High temperature-induced production of unreduced pollen and its cytological effects in Populus - Jun Wang (Nature Portfolio, 2017)
Abstract Temperature change is of potential to trigger the formation of unreduced gametes. In this study, we showed that short periods of high temperature treatment can induce the production of 2n pollen in Populus pseudo-simonii Kitag. The meiotic stage, duration of treatment, and temperature have significant effects on the induction of 2n pollen. Heat stress resulted in meiotic abnormalities, including failure of chromosome separation, chromosome stickiness, laggards and micronuclei. Spindle disorientations in the second meiotic division, such as parallel, fused, and tripolar spindles, either increased in frequency or were induced de novo by high temperature treatment. We found that the high temperature treatment induced depolymerisation of meiotic microtubular cytoskeleton, resulting in the failure of chromosome segregation. New microtubular cytoskeletons were able to repolymerise in some heat-treated cells after transferring them to normal conditions. However, aberrant cytokinesis occurred owing to defects of new radial microtubule systems, leading to production of monads, dyads, triads, and polyads. This suggested that depolymerisation and incomplete restoration of microtubules may be important for high temperature-induction of unreduced gametes. These findings might help us understand how polyploidisation is induced by temperature-related stress and support the potential effects of global climate change on reproductive development of plants.